Pengaruh Religiusitas terhadap Integriras Pegawai di DPRD Kota Bukittinggi - Hartinah Hartinah; Syamsir Syamsir (Policy, Law and Political Research Center, 2022)
This study aims to determine how much influence the employee religiosity in the DPRD of Bukittinggi City has. The method used is quantitative with descriptive method. In this study the population is all employees in the DPRD Bukittinggi. The number of samples in this study were 61 respondents drawn using the Yamane formula with a significance level of 5%. The sampling technique in this study is Proportional Random Sampling. The data collection technique in this study used a questionnaire that was distributed to respondents with a Likert scale measurement. The data analysis in this study was simple linear regression using SPSS version 16.0. The results showed that: 1) Based on the results of the description of the respondents' religiosity, the employees of the DPRD Kota Bukittinggi were in the very high category with a mean value of 3.30 with a percentage of 82%. . 2) The integrity of the Bukittinggi City DPRD employees is categorized as very high with an average score of 3.35 with a percentage of 84%. 3) There is a significant influence of religiosity on the integrity of employees in the DPRD Kota Bukittinggi with a significance value of 0.001 <0.05, and a T count value of 3.672 > T table 2.001 and an Adjusted R Square value of 0.172.